Redesigning the College of Education Curriculum to meet the Learner Centered Approach Needs of the Pre-service teacher for Effective Implementation of the Standard Based Curriculum in Ghana - Yekple, Sampson, L.K; Kumi, John-Newton; Kumah, Maxwell, S. (Journal of Education and Practice, 2022)
Purpose: There is the need for the training of Pre-Service Teachers (PST) to appreciate and exhibit Learner Centered Approach (LCA) in the teaching and learning process. As we celebrate the preparedness of the college of education tutors to impart this knowledge to the PST, the space to deliver is faced with challenges. This paper aims at exploring how tutors are implementing the practices in LCA in colleges of education in their lesson delivery. It also aims at populating the challenges associated with the implementing the approach. The paper in addition, aims at highlighting the possible practices that can support Pre-Service Teachers to appreciate the use LCA in facilitating concepts in the classroom. Methodology: This current qualitative research adopted exploratory and descriptive design. Qualitative data was collected through interview. Three Colleges of Education (CoE) in VOLTI zone were purposively sampled for the study. Result: From the interview results, it was found that, college curriculum on academic content is focusing much of its attention on academic content than practicum. The mode of assessment is also making the impartation of LCA to the pre-service teacher seemingly untenable. The college tutors are functionally equipped to impart the methodology of LCA to the pre-service teacher, however the use of the LCA does not support them co cover much curriculum content. Tutors struggle to complete the semester's curriculum hence a deviation from the low usage of the LCA. It is also noted that, quizzes and End of Semester examination assessment items do not reflect practicum. The observation results supportively confirm that tutors have difficulty of integrating LCA in the teaching of content related courses due to their apparent focus on examination. Unique Contribution to Theory, Policy and Practice: It is therefore concluded that, the current practice of promoting LCA without appropriate forms of assessment to sustain its practice demotivates both tutors and students to engage in such classroom practices. We therefore recommend that, the B.Ed program is reorganized to include more practicum to prepare functional PST in towards the facilitation of the Standard based Curriculum.